Rating scales measuring the severity of psychotic depression. (27th May 2015) - Østergaard, S. D.; Rothschild, A. J.; Flint, A. J.; Mulsant, B. H.; Whyte, E. M.; Leadholm, A. K.; Bech, P.; Meyers, B. S.
<x xml:space="preserve">Abstract</x> Objective Unipolar psychotic depression (PD) is a severe and debilitating syndrome, which requires intensive monitoring. The objective of this study was to provide an overview of the rating scales used to assess illness severity in PD. Method Selective review of publications reporting results on non‐self‐rated, symptom‐based rating scales utilized to measure symptom severity in PD. The clinical and psychometric validity of the identified rating scales was reviewed. Results A total of 14 rating scales meeting the predefined criteria were included in the review. These scales grouped into the following categories: (i) rating scales predominantly covering depressive symptoms, (ii) rating scales predominantly covering psychotic symptoms, (iii) rating scales covering delusions, and (iv) rating scales covering PD. For the vast majority of the scales, the clinical and psychometric validity had not been tested empirically. The only exception from this general tendency was the 11‐item Psychotic Depression Assessment Scale (PDAS), which was developed specifically to assess the severity of PD. Conclusion In PD, the PDAS represents the only empirically derived rating scale for the measurement of overall severity of illness. The PDAS should be considered in future studies of PD and in clinical practice.